Synthesis and Assessment of a New Tetrahydrogeraniol Derivative as Penetration Enhancer for Transdermal Drug Delivery - Khan, Amjad; Hanif Raja, Muhammad; Khan, Arshad; Wasim Khan, Muhammad; Majid Khan, Gul (Journal of Glycomics And Metabolism, 2016)
Background: Skin is one the most important sites for administration of drugs to obtain desired pharmacological effects either locally or through systemic bioavailability; and this has placed the transdermal route of drug delivery as an attractive and as one of the most innovative areas for conducting drug delivery research. However the stratum corneum in skin creates hurdles and acts as significant barrier for the permeation of drugs through skin. Penetration enhancers play a pivotal role to overcome such barriers and help enhance the permeation of drug through skin. However, penetration enhancement technology is challenging development and needs to be properly and skillfully addressed. Objective: The present investigation aimed to study the penetration enhancing effect of a newly synthesized alcohol derivative of an acyclic monoterpene (Tetrahydrogeraniol-THG). Methodology: The new derivative, 5,9-Dimethyl-1-Decanol (DIMDOL), has been synthesized by a chemical reaction of the THG with Grignard reagent and ethylene oxide. Permeation enhancing effect of the synthesized derivative was explored for better transdermal penetration of the two model drugs viz. tramadol hydrochloride and 5-fluorouracil (5-FU) through the excised rat skin by conducting in-vitro permeation experiments employing Franz diffusion cells apparatus. The standard enhancers Azone and THG were used to compare penetration enhancing effect of the enhancers. Results: It was revealed that DIMDOL could effectively enhance the permeability of both the drugs by 18.60 and 73.19 folds across the skin used with a lag time of 3.35 and 1.20 h, respectively. The newly synthesized derivative was found to significantly increase the partition coefficient and diffusion coefficient values. Conclusion: The results obtained suggest that DIMDOL can more effectively enhance the permeation of these model drugs, expectedly by affecting the stratum corneum and interacting with both lipid-rich layers and keratin-rich layers of the excised rat skin.
Keywords: Tetrahydrogeraniol; Penetration Enhancer; Transdermal Drug Delivery; Skin Permeation; 5-Fluorouracil; Tramadol Hydrochloride